Strategi Penanganan Banjir Rob Kota Pekalongan - Slamet Miftakhudin (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2021)
Pekalongan City is located in the lowlands of the northern coast of Java Island, experiencing tidal flooding with increasing frequency and area of inundation. Inundation due to tidal flooding that occurred in 2018 amounted to 1,391 hectares (29.97% of the total area) in 2020 increasing to 1,730 hectares (37.27% of the total area). The problem of tidal flooding occurred in 3 (three) sub districts covering 11 (eleven) Villages. National Medium-Term Development Plan (RPJMN) 2020 2024 mandates a major coastal protection project for 5 (five) urban areas including Greater Pekalongan. Various efforts have been made by various parties, including the Central Government, Central Java Provincial Government, Pekalongan City Government, Non-Governmental Organizations, Academics and other stakeholders to deal with the problem of tidal flooding in Pekalongan City. Seeing the dynamics of handling tidal floods in Pekalongan City carried out by various parties, it is necessary to research on strategies for handling tidal floods in Pekalongan City so that the handling carried out can be synergized and achieve targets effectively and efficiently. The purpose of this study was to formulate the strategy of tidal flood management in Pekalongan City and to determine the factors that influence. By analyzing Strengths, Weaknesses, Opportunities and Threats, the best strategy for handling tidal flooding in Pekalongan City will be obtained. The results of the study indicate the need for cooperation and coordination with various parties, community involvement and improvement of Human Resources to optimize the handling of tidal flooding in Pekalongan City. Keywords: Flood, tidal flood, Pekalongan